Analisis Faktor Muat Trans Metro Pekanbaru Koridor Terminal Bandar Raya Payung Sekaki (BRPS) - Kulim - Devita Anggraini; Yosi Alwinda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Trans Metro Pekanbaru (TMP) is public transportation that has been operating since 2009 in Pekanbaru. It has function to reduce the problems related to public transport and traffic that appear because of the development of the city itself. During the time, the changing of passenger quantity, service quality and operation could happen anytime. Therefore, this research was done to find out the effectivity of Trans Metro Pekanbaru corridor II that serves the transportation from Terminal Bandar Raya Payung Sekaki (BRPS) to Kulim with the load factor as the indicator. The aim of this research is to determine the value of load factor and analyze the characteristic of Trans Metro Pekanbaru route that refer to the changing of load factor value, especially to the corridor of Terminal BRPS- Kulim. The results of this research were TMP busses of Corridor II which were not effective yet if we concern from the number of passenger, because the most of the load factor on this corridor has not appropriate the standard load factor value yet, based on the SK Dirjen No. 687 at 2002 (70%), so it was not optimal in serving the movement of passengers. Based on the result of the analysis, the characteristics of Trans Metro Pekanbaru Corridor II has value load factor greater than 70% were in the holiday period from Terminal Bandar Raya Payung Sekaki to Kulim was the Kantor Pos shelter - Metro Plaza 1 shelter that is a transit shelter in the city center and shelter at the shopping center. From the results of statistical tests that have been performed, the selection mode equation Trans Metro Pekanbaru is : Y = 5.75 - 0.061 X1 + 0.008 X2 + 0.000 X3 + 0.005 X4. Attributes considered is the waiting time (X1), speed (X2), rate (X3) and the convenience vehicles (X4). Keyword : Trans Metro Pekanbaru, load factor, regression, stated preference